Aural Souvenirs: temporal disruption and formal coherence in John Zorn’s Cat O’ Nine Tails (Música Hodie, 2013)
Commissioned by the Kronos Quartet in 1988, Zorn’s string quartet Cat O’ Nine Tails originated as a “filecardcomposition”, but was eventually assembled as a conventionally notated score. Subtitled “Tex Avery directs theMarquis de Sade,” the fifteen-minute work combines a variety of musical quotes, stylistic allusions, improvisationalepisodes, and noise elements in a frenetic and dramatic musical collage. A continuous play of fragmented and disjunctivereferentiality, Cat O Nine Tails exemplifies late twentieth century postmodernism. This paper provides an analysisof the musical structure of Cat O’ Nine Tails. By applying music theorist Jonathan D. Kramer’s hierarchy of linearityand nonlinearity as an analytical model, I attempt to address Zorn’s idiosyncratic approach to time and context,and discuss how the composer simultaneously disrupts and maintains structural integrity and compositional intent.Keywords: John Zorn; Cat O’ Nine Tails; Music for string quartet; Jonathan D. Kramer; Postmodernism in music;Moment form.